Assessment of erosion and hazard in the coastal areas of Selangor - Hamizah Ahmad,; Khairul Nizam Abdul Maulud,; Othman A. Karim,; Fazly Amri Mohd, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Sea level rise is often associated with climate change and global warming. The change in shoreline is a continuous process that occurs through various processes such as erosion, sedimentation, sea level rise, wave behaviour and land use. Rapid technological advancement has made it possible to quickly identify the shoreline changes through a combination of Geographical Information Systems (GIS) application and Remote Sensing technology. The current study aims to identify the criteria or characteristics of the coastal areas and identify the risks for potential hazards in the coastal areas of Selangor. The data used in this study are the topographic maps produced in 1984 and SPOT 5 satellite images taken in 2013. The results of this study show that the estimated total area of erosion is 2,558 hectares and the total area of accretion is 2,583 hectares. The areas in Pasangan, Tanjong Karang, Api-Api, Bagan Nakhoda Omar, Jeram, Pasir Panjang, Hujong Permatang, Kuala Selangor and Panchang Bedena are categorized as critical erosion areas. Risk assessment analysis was done to identify the risk levels of coastal erosion hazards. Results indicate that the risk level for human, social and economic components is low while the level for infrastructure components ranges between low and moderate. However, the risk for coastal erosion hazards for the environment is high. The results of this study provide the critical information required by government agencies to formulate policies and implement an Integrated Coastal Management Plan in the effort to effectively deal with climate change and sea level rise phenomenon.